EFEKTIVITAS MANAJEMEN KOMITE SEKOLAH DALAM PENGELOLAAN PENDIDIKAN - Nur Gamar; Putriani L. Maliki (Tadbir: Jurnal Manajemen Pendidikan Islam, 2023)
This study aims to see how effective school committee management is in managing education. The method used is library research or commonly called library research in which research data is obtained from books and other literature both print and online which are then analyzed theoretically-philosophically. The results of the study show that one of the determining factors in maintaining the quality of education is involving the school committee, namely by involving it massively in every process that exists in every school. Because, his presence can contribute positive suggestions, thoughts, ideas and ideas, which can be the basis for doing something even better in the management of an educational institution